Moral Apes, Human Uniqueness, and the Image of God - Putz, Oliver (Zygon, 2009)
Abstract. Recent advances in evolutionary biology and ethology suggest that humans are not the only species capable of empathy and possibly morality. These findings are of no little consequence for theology, given that a nonhuman animal as a free moral agent would beg the question if human beings are indeed uniquely created in God's image. I argue that apes and some other mammals have moral agency and that a traditional interpretation of the imago Dei is incorrectly equating specialness with exclusivity. By framing the problem in terms of metaphor, following the work of Paul Ricoeur and Sallie McFague, I propose that the concept of the imago Dei could be extended to accommodate moral species other than our own.